Batik Artisans’ judgment of batik wax quality and its criteria: An application of the Many-facet Rasch Model - Kudiya, Komarudin; Sumintono, B.; Sabana, Setiawan; Sachari, Agus (Springer, 2018)
Batik is a traditional dyeing technique that uses hot melted wax on natural fabric. The wax is applied to the fabric, left to dry, then the fabric is dyed using cold water dyes. Wax quality is central to the batik process and, in the Indonesia region, there are ten standard criteria used to measure the batik wax quality. This study used five batik wax samples tested by twenty batik artisans according to those standard evaluation criteria, and the ensuing data were analyzed using the many-facets Rasch Model. The study found that one criterion, the cost of wax making is regarded as the most difficult item for the batik artisans to endorse. Two criteria for judging batik wax quality, namely ‘easy to set’ and ‘not sticky’ are two items that elicited unexpected responses from raters.